Zginanie i Skręcanie Osiowo-Symetrycznej Płyty o Dyskretnej Strukturze - Śliżewicz, J. (Engineering Transactions, 1971)
On the basis of the theory of a discrete medium introduced by H. Frąckiewicz, an axi-symmctric a plate was dissolved, loaded axial-symmetrically with forces perpendicular to the plane and vectors of moments lying in the plane of a plate. The general solutions have been obtained from the dislocated equations determining a set of a three differential linear equations having changeable coefficients. In the concrete examples, the dislocations and stresses were found facultative constants being calculated from the boundary conditions.